Outcome of patients with breast cancer in the oldest old (≥80 years). (January 2020) - Fleurier, Claire; De Wit, Adeline; Pilloy, Joseph; Boivin, Laura; Jourdan, Marie-Lise; Arbion, Flavie; Body, Gilles; Ouldamer, Lobna
Abstract: Purpose: In the present study, we present a large institutional study to determine the influence of age≥ 80 years on breast cancer presentation and prognosis. Methods: The study is a retrospective analysis of our prospectively maintained breast cancer database study using data from of women managed from January 2007 through December 2013. Clinicopathologic characteristics were correlated with outcomes according to age (<80 years and ≥ 80 years). Results: During the study period, 2083 women with invasive breast cancer were included of which 160 women aged ≥ 80 years (7.7 %). Overall survival was lower in the oldest old than in younger counterparts (p < 0.0001) as was distant metastasis free survival (p = 0.004). Differences in management included more radical surgeries and less chemotherapy and radiotherapy in case of age≥ 80 years. By multivariate analysis, age ≥ 80 years was an independent predictive factor of poor overall survival. Conclusion: In the present study, age ≥ 80 years was an independent predictive factor of poor overall survival.